Pengaruh Teman Sebaya Bagi Pertumbuhan Spiritualitas Remaja Di Jemaat GMIST Musafir Manado - Pesak, Natalia; Poguman, Prince Nuriani; Riung, Notangli Paildi; Pangalo, Hanggita Halena; Lelerang, Widyawati Berni; Goha, Freis Anatasya Goha; Sasombo, Novianti Jessica; pontoh, Sisilia; Suleman, Jennyver Putry Theresia; Pananggung, Rifke Alfione; Salanggamo, Inriyani; Imbar, Syaloomita Imanuela Imbar; Tahulending, Mario (HOSPITALITAS: Jurnal Pengabdian Kepada Masyarakat, 2024)
This research examines the influence of peers on the spiritual growth of teenagers in the GMIST Musafir Manado congregation. Using a descriptive qualitative approach, this research involved interviews and group observations of teenagers who were active in the church. The research results show that peers play an important role in shaping adolescent spirituality. Peers who are supportive and have positive values ​​help teenagers develop an optimistic and resilient attitude. Conversely, negative influence from peers can cause deviant behavior and psychological problems. Therefore, families, educators and society need to provide consistent guidance and support. These findings can help churches and parents create environments that support teens' spiritual growth.